Islamic based Rational Emotive Behavior Therapy Approach Group Counseling to Reduce Delinquent Behaviors (Universitas Negeri Semarang, 2019)
This study was conducted at Public Islamic High School 2 Semarang (MAN 2 Ito examine the effectiveness of Islamic-based REBT approach group counseling to reduce students’ delinquent behaviors. For more, the study belonged to experimental study with the design of pre-test – post-test control group, and involved fourteen eleventh grade students. Their data were collected through the adapted instrument of activities delinquent scale resulted from Paired sample t-test. Based on the results of paired sample t-test, it was known that the Islamic-based REBT approach group counseling was effective to reduce students’ delinquent behaviors (t(6) = 7.36, p < 0.01). This finding confirms that the Islamic-based REBT approach group counseling implemented through akhlak (good character), sholat (Islamic worship), fasting, dhikr, and prayer is effective to reduce students’ delinquent behaviors.